2021
DOI: 10.1002/2688-8319.12036
|View full text |Cite
|
Sign up to set email alerts
|

The list of vascular plants for the city of Toronto

Abstract: 1. Urban areas have become epicentres for applied ecological and conservation research and policy. Yet, most urban areas have surprisingly little consolidated information about their biota, including species-at-risk and invasive species. 2. I used multiple data sources to compile a list of vascular plants for the greater metropolitan Toronto region. This data not only includes taxonomic information but also global and national status ranks, growth from, native status, threatened status, abundance estimates and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Our results also show that larger cities (both in terms of area and population size) support more species in total and in the various plant groupings, as has been shown previously (Pyšek, 1998;Veselkin et al, 2017;Tretyakova et al, 2018). The cities examined here harbor substantial numbers of alien taxa, more than 30% of the urban flora, which is remarkably similar to other urban plant analyses (Ricotta et al, 2009;Aronson et al, 2014;Cadotte, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results also show that larger cities (both in terms of area and population size) support more species in total and in the various plant groupings, as has been shown previously (Pyšek, 1998;Veselkin et al, 2017;Tretyakova et al, 2018). The cities examined here harbor substantial numbers of alien taxa, more than 30% of the urban flora, which is remarkably similar to other urban plant analyses (Ricotta et al, 2009;Aronson et al, 2014;Cadotte, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The highest numbers of alien plants are concentrated in urban floras where purposeful introductions and environmental changes are most apparent (Aronson et al, 2014;Potgieter and Cadotte, 2020). Globally, it has been shown that cities generally harbor a high diversity of alien plant species; frequently between 25 and 50% of urban floras are classified as alien (Ricotta et al, 2009;Cadotte, 2020). The presence of alien plants influences the overall composition and structure of urban floras (Ricotta et al, 2009(Ricotta et al, , 2012Cadotte, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban areas can provide substantial plant biodiversity, but greater abundance and species richness do not always equate to suitable quality habitat for urban wildlife. Between 30% and 50% of urban plant species are non-native [79][80][81][82]. Non-native plant species abundance and richness increase in more urbanized environments [83], a process driven by human-mediated trade and transport, whether that be unintentional or intentional [84].…”
Section: Urban Vegetation: Benefits Constraints and Effects On Urban ...mentioning
confidence: 99%